2020
DOI: 10.3390/s20123455
|View full text |Cite
|
Sign up to set email alerts
|

Development of Taste Sensor to Detect Non-Charged Bitter Substances

Abstract: A taste sensor with lipid/polymer membranes is one of the devices that can evaluate taste objectively. However, the conventional taste sensor cannot measure non-charged bitter substances, such as caffeine contained in coffee, because the taste sensor uses the potentiometric measurement based mainly on change in surface electric charge density of the membrane. In this study, we aimed at the detection of typical non-charged bitter substances such as caffeine, theophylline and theobromine included in beverages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…In the study [35], the interactions between caffeine and HBA were formed by intermolecular hydrogen bonds (e.g., the O-H(carboxy) N(imidazole) hydrogen bond). On the basis of this result, the study [13] has discussed the mechanism of caffeine detection as the following: owing to intermolecular hydrogen bonds between HBAs and caffeine, the carboxyl groups of HBAs removed H + from the caffeine solution, which caused allostery. The allostery resulted in a change in membrane potential, which is used as the response to caffeine.…”
Section: Mechanism Of Caffeine Detection Using Taste Sensor With Lipi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study [35], the interactions between caffeine and HBA were formed by intermolecular hydrogen bonds (e.g., the O-H(carboxy) N(imidazole) hydrogen bond). On the basis of this result, the study [13] has discussed the mechanism of caffeine detection as the following: owing to intermolecular hydrogen bonds between HBAs and caffeine, the carboxyl groups of HBAs removed H + from the caffeine solution, which caused allostery. The allostery resulted in a change in membrane potential, which is used as the response to caffeine.…”
Section: Mechanism Of Caffeine Detection Using Taste Sensor With Lipi...mentioning
confidence: 99%
“…In our previous study [13], non-charged bitter substances (e.g., caffeine, theophylline, and theobromine) were measured using taste sensors with lipid/polymer membrane modified with HBAs, and this method is similar to those which improve the sensitivity of sweet taste sensors to sugar by surface modification [14,15]. In the literature [13], caffeine detection has been discussed as a change in membrane potential due to allostery caused by intermolecular hydrogen bonds between HBAs and caffeine. Moreover, the sensitivity of taste sensors to caffeine detection has been related to the number of intramolecular hydrogen bonds of HBAs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that alkaloids such as caffeine, theophylline, and theobromine provided bitter taste in teas, and caffeine was a main contributor to bitterness. Furthermore, flavonoids, catechins, and certain amino acids including L -histidine, Llysine, L -valine, L -tryptophan, L -arginine, L -tyrosine, Lphenylalanine, L -isoleucine, and L -leucine, contributed to bitter taste in teas (Yang et al 2018;Zou et al 2018;Yoshimatsu et al 2020). L -Theanine, L -glutamic acid, L -glutamine, L -aspartic acid, and L -asparagine contributed to the umami taste (Yang et al 2018).…”
Section: Scores Of the Taste Strength In Fbt Samplesmentioning
confidence: 99%
“…The average of the third to fifth measurement cycle was calculated as the response value. The standard deviations were calculated from n = 4 (sensor electrodes) × 3 (cycles) = 12 values in the same way as previous studies [10,17,20,27].…”
Section: Measurement Procedures Of Taste Sensormentioning
confidence: 99%